Standards and their practical use in powder handling procedures and reuse in industrial laser-based powder bed fusion of metals - Lehtihuhta, Erkka (My University, 2024)
Additive manufacturing is a process of making objects to make parts from 3D-model data, usually layer upon layer, as conversely to conventional manufacturing methods. The rapid development within the branch of additive manufacturing has resulted that standardization of materials, procedures, equipment etc. are left more or less behind in this expansion. This lack of standards can even be the main reason of the slow adoption of additive manufacturing technology. There are various technologies within additive manufacturing, one of the most widely used being laser-based powder bed fusion. In this method it is possible to reuse the metal powder remaining intact after producing a final part. Reusing practice reduces the manufacturing costs of the product, thus making powder bed fusion economically more feasible as a choice for manufacturing. This thesis concentrates on standards related to powder reuse in laser-based powder bed fusion. This thesis is a part of a larger project, DREAMS (Database for Radically Enhancing Additive Manufacturing and Standardization). This project is the first systemic AM development project in Finland, and it has potential to boost the Finnish AM industry widely. There is also a large-scale American co-project going on since 2016, aiming to globally fill the gaps in additive manufacturing standards. One of standards, published in 2021 (ASTM F3456-22, Standard Guide for Powder Reuse Schema in Powder Bed Fusion Processes for Medical Applications for Additive Manufacturing Feedstock Materials) is the core in this thesis. In this standard seven (7) different powder reuse schemes are defined. Based on these different modes of powder reuse, a questionnaire was sent to Finnish additive manufacturing companies to gain understanding about powder reuse in practice. Also a few interviews were carried out to deepen the results. The results of the questionnaire and interviews show that there are different schemes for powder reuse among AM manufacturers, as expected. Sieves of specified mesh size are needed in reuse procedures, and there was a lot of variation between the sieves that were applied. Sometimes the size of the sieve was not even known accurately. Also, when new powder was to be added, the exact amount of this new powder was poorly followed. Powder reuse history seems to be documented well enough, but not in a standardized way. Powder handling procedures were in most cases not certified, but customers rarely asked anything about powder handling. Based on the answers given by Finnish additive manufacturing industry companies even this limited amount of research material shows that powder handling and reuse procedures are far from being standardized. This thesis reveals an urgent need to find ways of standardizing powder reuse practices as one part in an attempt to raise the quality of Finnish additive manufacturing industry to next level. Further studies may follow as new standards are being published – even if are yet not recognized as international standards, like in this case. All this can by now done in a coordinated fashion by DREAMS project.
Keywords: Additive manufacturing, laser-based powder bed fusion, metal, standard, powder handling, powder reuse, procedure, quality